Islamic leadership at the International Islamic University Malaysia - Ahmad , Khaliq; Harvey Fontaine, Rodrigue Ancelot (International Islamic University Malaysia, 2011)
This paper is an empirical study related to Islamic leadership. The literature review of this paper focuses on transactional leadership, transformational leadership and servant leadership. The literature suggests that Islamic leadership most closely resembles servant leadership. A questionnaire was then used to assess how administrators at the International Islamic University Malaysia (IIUM) view the leadership approaches of their direct superiors and which leadership approach they prefer. The results of the survey clearly indicate that they prefer servant leadership followed by transformational leadership. Respondents dislike transactional leadership. The implications of the studies are discussed and the possibility of generalization is discussed.